Pediatric temporal bone rhabdomyosarcoma. Issue 8 (August 2016) - Goldberg, Monica J.
Abstract : ABSTRACT: Rhabdomyosarcoma is one of the most common soft-tissue sarcomas in children. Prompt diagnosis and treatment significantly improve survival; however, misdiagnosis is common because of this aggressive temporal bone lesion's similarity to more common benign diseases. Clinicians should maintain a high index of suspicion for rhabdomyosarcoma in patients with a presumed otologic infection not responsive to medical therapy.